The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/jfmm-11-2021-0296
|View full text |Cite
|
Sign up to set email alerts
|

Investigating consumers' brand desirability of “upcycled” luxury: the many faces of designer facemasks

Abstract: PurposeThe purpose of the study is to investigate the effect of terminal and instrumental values on the attitude and brand desirability for upcycled luxury designer facemasks, in relation with generic luxury designer facemasks.Design/methodology/approachA quantitative approach was adopted in this study, and data were collected via an online consumer panel from 390 existing Australian luxury consumers, aged 18 and above. Stimuli that represented the two upcycling conditions (remnants and past collections) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The findings also show that the instrumental value "responsibility" may have multiple meanings as a mean to diverse terminal values: it is a mean to a consumer's pleasure (making responsible choices can make one feel good), to a wider ethical viewpoint (doing or not doing good to others) and to the ethicality of the corporate brand (ensuring one's financial security with a loyalty card system). This is in line with the research suggesting that terminal values refer to preferred social, emotional, aesthetic and self-expressive end-states of existence (Kahle, 1986;Kautish and Sharma, 2018;Phau et al, 2022aPhau et al, , 2022b and are based on universal needs of individuals such as hedonism (pleasure), security (financial security) and universalism (doing good) (Allen, 2001;Schwartz, 1994). While the findings are also in line with research that has considered pleasure as one possible terminal value in the decision of purchasing luxury products (Kautish et al, 2020), it extends this line of research by highlighting the important role of doing good and showing that monetary incentives may have an underlying influence on consumers' purchasing decisions regarding premium PL brands.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings also show that the instrumental value "responsibility" may have multiple meanings as a mean to diverse terminal values: it is a mean to a consumer's pleasure (making responsible choices can make one feel good), to a wider ethical viewpoint (doing or not doing good to others) and to the ethicality of the corporate brand (ensuring one's financial security with a loyalty card system). This is in line with the research suggesting that terminal values refer to preferred social, emotional, aesthetic and self-expressive end-states of existence (Kahle, 1986;Kautish and Sharma, 2018;Phau et al, 2022aPhau et al, , 2022b and are based on universal needs of individuals such as hedonism (pleasure), security (financial security) and universalism (doing good) (Allen, 2001;Schwartz, 1994). While the findings are also in line with research that has considered pleasure as one possible terminal value in the decision of purchasing luxury products (Kautish et al, 2020), it extends this line of research by highlighting the important role of doing good and showing that monetary incentives may have an underlying influence on consumers' purchasing decisions regarding premium PL brands.…”
Section: Discussionsupporting
confidence: 91%
“…Recent research has shown that both instrumental and terminal values affect consumers’ behavioral intentions (Kautish and Sharma, 2018). For instance, researchers have proposed that terminal value-oriented individuals seek social or individual benefits by consuming products that offer them symbolic and expressive benefits, while instrumental value-oriented individuals value a product's utilitarian benefits over hedonic benefits (Allen et al , 2002; Phau et al , 2022a, 2022b). The purchase decision of premium brands is often motivated by different reasons than that of economy products.…”
Section: A Conceptual Framework For the Emergence Of A Values-based P...mentioning
confidence: 99%
“…Upcycling is to create higher quality and value‐added products through a redesigning process of discarded raw materials or objects (Sung, 2015). The potential for upcycled products to be transformed from superfluous materials into something valuable and attractive (Phau et al, 2022) has led to mass sales of upcycled products by numerous evolving firms of impending evolution in the context of sustainability innovation (McDonough & Braungart, 2002). The scope of products created through upcycling has varied across different categories, such as rugs from fabric scraps, refashioned clothes or bags; soaps and fertilizers from organic waste, artistic objects from scrap metal; or even an entire building from reused deconstruction components (Sung, 2017; Yu & Lee, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The need for companies to reduce waste, improve revenue, and gain a positive corporate image as ethical companies have resulted in the common trend of upcycling (Phau et al, 2022). Upcycling is further considered the greener version of recycling.…”
Section: Upcycled Luxury Fashionmentioning
confidence: 99%
See 1 more Smart Citation